Effects of the Minimum Wage on Working Time - Toralf Pusch; Hartmut Seifert; Chiara Santoro (Wirtschaftsdienst)
Abstract Five years after the introduction of the statutory minimum wage, numerous well-founded evaluation analyses are available. The effects of minimum wage on working time are of particular relevance; they have an impact on income development and the volume of work in the low-wage sector. Against this background, our contribution offers an up-to-date analysis from the IAB’s PASS data set, which has been little used to date and is particularly suitable for the analysis of the low-wage sector. It shows that reductions in working hours have occurred mainly among those in marginal employment and recipients of social transfers, which is probably partly due to a reaction of the labour supply.